Prevalence and Characteristics of Obsessive-Compulsive Disorder Among Urban Residents in Wuhan During the Stage of Regular Control of Coronavirus Disease-19 Epidemic - Zheng, Yage; Xiao, Ling; Xie, Yinping; Wang, Huiling; Wang, Gaohua (Frontiers in Psychiatry, 2020)
Background: Coronavirus disease-19 (Covid-19) is one of the most devastating epidemics in the 21st century, which has caused considerable damage to the physical and mental health of human beings. Despite a few regions like China having controlled the epidemic trends, most countries are still under siege of COVID-19. As the emphasis on cleaning and hygiene has been increasing, the problems related to obsessive-compulsive disorder (OCD) may appear. Objective: This study was designed to investigate the prevalence of OCD in the urban population in Wuhan during the stage of regular epidemic control and prevention. Meanwhile, characteristics and risk factors for OCD were also explored. Method: Five-hundred and seventy residents in urban areas of Wuhan were recruited using the snowball sampling method to complete questionnaires and an online interview from July 9 to July 19, 2020. Collected information encompassed socio-demographics, Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) scores, Social Support Rating Scale (SSRS) scores and Pittsburgh Sleep Quality Index（PSQI) values. Results: Three months after lifting the quarantine in Wuhan, the prevalence of OCD was 17.93%. About 89% of OCD patients had both obsessions and compulsions, while 8% had only obsessions and 3% had only compulsions. Top 3 common dimensions of obsessions were miscellaneous (84.0%), aggressive (76.6%), and contamination (48.9%), and of compulsions were miscellaneous (64%), checking (51.7%), and cleaning/washing/repeating (31.5%). The unmarried were more vulnerable to OCD than the married (p<0.05, odds ration=1.836). Students had 2.103 times the risk of developing OCD than health care workers (p<0.05). Those with positive family history of OCD and other mental disorders (p<0.05, odds ration=2.497) and presence of psychiatric comorbidity (p<0.05, odds ration=4.213) were also at higher risk. Each level increase in sleep latency increased the risk of OCD to 1.646 times(p<0.05). Conclusion: In the background of regular epidemic control, the prevalence of OCD was high, and the symptoms were widely distributed. Obsessions often accompanied compulsions. Being single and a student, positive family history of OCD and other mental disorders, presence of psychiatric comorbidity, and longer sleep latency were predictors of OCD. Early recognition and detection of these issues may help to intervene in OCD.